A comprehensive quantitative analysis of jaywalking citations for New York City from 2006 to 2022 - Murray, Abigail (Journal of ethnicity in criminal justice, 2025)
Previous studies of jaywalking enforcement have mainly focused on individual-level analyses of the disproportionate number of tickets received by minority individuals. Such research does not account for community-level variables that could affect findings. To address this gap, we have conducted a comprehensive study of the relationship between the number of jaywalking tickets and variables such as poverty, walking to work, street type, and race for census tracts in New York city across three different censuses. Our results indicate disproportionate enforcement of jaywalking across different census tracks, with population makeup being a consistent predictive factor.